KnockoutJS essentials : implement a successful JavaScript-rich application with KnockoutJS, jQuery, and Bootstrap - Ferrando, Jorge (Community experience distilled., 2015)
If you are a JavaScript developer who has been using DOM manipulation libraries such as Mootools or Scriptaculous, and you want go further in modern JavaScript development with a simple and well-documented library, then this book is for you. Learning how to use Knockout will be perfect as your next step towards building JavaScript applications that respond to user interaction.